(untitled) (PJDOL, 2023)
The use of social media, particularly Facebook has grown tremendously popular and is increasing fast with every coming day. Most of the users happen to be students of higher education institutions, so it is pertinent to explore the nature of its use by university students, the harms associated with it and the issue of Facebook for spreading religious posts.